Sternoclavicular sinus: Case series and literature review of a rare head and neck lesion. (October 2019) - Luu, Kimberly; Valenzuela, Dianne; Chadha, Neil K.; Moxham, Paul
Abstract: Objective: The objective of this study is to describe the clinical and pathologic features of a rare congenital neck anomaly, a sternoclavicular sinus, and review the literature on this topic. Study design: This study is a retrospective case series of four subjects diagnosed with a sternoclavicular sinus. Methods: Patients with a congenital neck anomaly, distinct from common branchial cleft anomalies, were identified through a 10-year retrospective chart review of a tertiary care pediatric otolaryngology practice. Results: We describe four patients with a congenital neck anomaly with common features of a sternoclavicular anomaly. All patients presented with a superficial neck anomaly adjacent to the sternoclavicular joint. Surgical excision through an external approach was successfully performed in three out of the four patients with subsequent resolution of symptoms. The literature review compiles all the cases presented. Theories on embryologic origin include incomplete fusion of sternum and clavicle or unusual remnant of a fourth branchial cleft. Commonalities include left sided predominance, squamous epithelium lined sinus tract ending at the sternoclavicular junction, and successful surgical excision in almost all cases. Conclusion: A sternoclavicular sinus is a rarely described congenital neck abnormality. Presentation and management is similar to branchial cleft anomaly but with a distinct anatomical pathway that is important for surgeons to recognize. Level of evidence: This manuscript presents a case series. The level of evidence proposed is Level 4.